PENERAPAN STRATEGI PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SDN 006 REDANG KECAMATAN RENGAT BARAT KABUPATEN INDRAGIRI HULU - Syarifah Nurhayati; Eddy Noviana; Otang Kurniaman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research was motivated by the facts that occurred in the fourth grade SDN 006 Redang Kecmatan Rengat Bangat their students do not master the subject matter IPA. The problem of this research is "Does the implementation of inquiry learning strategies to improve learning outcomes for teaching science Grade IV SDN 006 Redang Kecmatan Rengat Bangat?". The purpose of this research to improve learning outcomes of science subjects Grade IV through the implementation of inquiry learning strategy at SDN 006 Redang Kecmatan Rengat Bangat. This research is located at 006 State fourth grade SDN 006 Redang Kecmatan Rengat Bangat and held on 5 April 2016 until 21 April 2016 with a number of subjects as students of 20 people consisting of 6 female students and 14 male students. This research is a classroom action research conducted in two cycles. Based on the results the percentage learning outcomes in basic score, an average of 60 to UH I with an average of 68.25 with a margin increase of 13.75%, while on the UH UH I to II average of 82% with a margin increase of 20.14% difference. Improving student learning outcomes from initial data until the second cycle as a whole amounted to 33.89%. Based on the above it can be concluded the implementation of inquiry learning strategies (SPI) can improve learning outcomes science subjects Grade IV SDN 006 Redang Kecmatan Rengat Bangat Keywords: Inquiry Learning Strategy, Learning Outcomes, IPA